Functional outcomes and reading performance after combined implantation of a amall-aperture lens and a segmental refractive bifocal lens - Son, Hyeck Soo; Khoramnia, Ramin; Yildirim, Timur Mert; Baur, Isabella; Łabuz, Grzegorz; Auffarth, Gerd U. (Journal of refractive surgery, 2019)
Purpose: Clinical evaluation of the visual outcomes after implantation of a small-aperture extended depth of focus (EDOF) intraocular lens (IOL) and a segmental refractive bifocal lens. Methods: In this prospective study, 13 patients with cataract received a small-aperture IC-8 IOL (AcuFocus, Irvine, CA) in one eye and a segmental-refractive Lentis Mplus LS-313 MF20 IOL (Oculentis, Berlin, Germany) in the fellow eye. The clinical examination included measurements of uncorrected (UDVA) and corrected (CDVA) distance visual acuity, uncorrected (UIVA) and distance-corrected (DCIVA) intermediate visual acuity, and uncorrected (UNVA) and distance-corrected (DCNVA) near visual acuity. Additionally, a defocus curve was obtained from +2.00 to −5.00 diopters (D) and a Salzburg Reading Desk was used to assess the patients' reading acuity at intermediate and near distances. A halo and glare simulator was used to evaluate the postoperative perception of dysphotopsia. Results: At 5 months postoperatively, the mean binocular visual results demonstrated UDVA, UIVA, and UNVA values of −0.04 ± 0.11, 0.00 ± 0.10, and 0.11 ± 0.08 logMAR, respectively. The binocular distance-corrected reading performance test also confirmed the improved visual function, with an intermediate reading acuity of 0.12 logMAR at 69.21 cm and a near reading acuity of 0.19 logMAR at 41.63 cm. The mean halo size was 32.54 ± 22.38, mean halo intensity was 34.46 ± 21.95, mean glare size was 9.00 ± 17.47, and mean glare intensity was 9.92 ± 16.84. Conclusions: The new concept of a combined implantation of a small-aperture IOL and a segmental-refractive bifocal lens showed good results in far and intermediate distances and functional results at near distance, while causing minimal photic phenomena.
Gesehen am 08.10.2019